PENTINGNYA KOMUNIKASI KELUARGA: MENELAAH POSISI IBU ANTARA MENJADI WANITA KARIR ATAU PENCIPTAAN KELUARGA BERKUALITAS - S. Bekti Istiyanto (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2007)
Being career woman in Indonesia is not strange right now. They allowed to go out from their home simply. On the other situation, many husbands complain about unbalancing situation to create a certain quality family, particularly about the children education. In fact, is is very difficult to be career woman and creating a certain quality family. An effort in using appropriate communication in a family becomes the important thing right now. Every component in a family should realize how to connect each others. Every family need an appropriate channel and understand how to send message for all the family members. So, becomes career woman is not in the wrong situation now but those understanding about an appropriate communication using is also very important. Here is the urgent position to understand how to communicate among family members through appropriate interpersonal communication is needed.